Barriers to the adoption of new safety technologies in construction: a developing country context - Yap, Jeffrey Boon Hui; Lam, Canwin Guan Ying; Skitmore, Martin; Talebian, Nima (Journal of Civil Engineering and Management, 2022)
The adoption rate of new technologies is still relatively low in the construction industry, particularly for mitigating occupational safety and health (OSH) risks, which is traditionally a largely labor-intensive activity in developing countries, occupying ill-afforded non-productive management resources. However, understanding why this is the case is a relatively unresearched area in developing countries such as Malaysia. In aiming to help redress this situation, this study explored the major barriers involved, firstly by a detailed literature review to identify the main barriers hampering the adoption of new technologies for safety science and management in construction. Then, a questionnaire survey of Malaysian construction practitioners was used to prioritize these barriers. A factor analysis further identified six major dimensions underlying the barriers, relating to the lack of OSH regulations and legislation, technological limitations, lack of genuine organizational commitment, prohibitive costs, poor safety culture within the construction industry, and privacy and data security concerns. Taken together, the findings provide a valuable reference to assist industry practitioners and researchers regarding the critical barriers to the adoption of new technologies for construction safety management in Malaysia and other similar developing countries, and bridge the identified knowledge gap concerning the dimensionality of the barriers.